Herd behaviour along the consumer buying decision process - experimental study in the mobile communications industry - Pavlović-Höck, Nataša (Digital Business, 2022)
With the dissemination of web technologies, the transparency of other people's opinions has increased tremendously, thus the possibilities of observing other consumers' decisions have also risen. Consumers may take a shortcut to follow a herd — according to which people discount their own information to imitate others. Nonetheless, despite a large body of literature exploring the topics of herd behaviour, little is known about it in the context of the individual decision-making phases before, during, and after buying. This study, examines consumers' decisions in the context of mobile communications products, using a survey experiment. The findings show that subjects use the information from others as cues in making buying decisions, whereby the influence decreases along the buying process and in the post-buying phase, where people no longer seem to follow the herd. Additionally, recommendations of other consumers exert a stronger influence on subject choices than those of experts. Finally, friends seem to influence consumers' choices more than social networks.
CRIS-Team Scopus Importer:2024-12-16
Keywords: buying decision process; Herd behavior; information source; mobile communications industry